Peran Ketua Program Studi Pendidikan Seni Rupa dalam Pengembangan Kurikulum MBKM Tahun 2020 - Tantra Sakre; Dedi Kuswandi; Otto Fajarianto (Institut Agama Kristen Negeri (IAKN) Ambon, 2025)
Abstract: This study aims to examine the role of the Head of the Fine Arts Education Study Program at Universitas PGRI Adi Buana Surabaya in the development of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in 2020. The research employs a qualitative approach with a phenomenological design, involving the Head of the Study Program, curriculum team lecturers, faculty leaders, and students as the primary data sources. Data collection techniques include participatory observation, in-depth interviews, and documentation studies of the MBKM curriculum. The findings reveal that the Head of the Study Program functions as a coordinator, motivator, supervisor, and collaborator in the process of designing and implementing the MBKM curriculum. The coordinator role is evident in determining graduate profiles, formulating learning outcomes, and structuring the curriculum to accommodate MBKM activities. The motivator role is reflected in efforts to encourage lecturers and students to participate in MBKM programs and art activities beyond campus. The supervisor role is demonstrated through monitoring the implementation of learning and converting MBKM activities into courses. The collaborator role is shown in developing networks with schools, art communities, and partner institutions as venues for MBKM programs. Supporting factors in the development of the MBKM curriculum include institutional support, lecturer commitment, and student enthusiasm; while obstacles involve limited initial understanding of MBKM policies, administrative challenges in credit conversion, and the availability of suitable partners in the field of fine arts. Keywords: Role Of Study Program Head, MBKM Curriculum, Fine Arts Education